Subduction zone polarity in the Oman Mountains: Implications for ophiolite emplacement - Searle, M; Warren, C; Waters, D; Parrish, R (2003)
Two end-member models have been proposed to account for the structure and metamorphism of rocks beneath the Semail ophiolite in the Oman mountains. Model A involves a single, continuous NE-directed subduction away from the continental margin during the late Cretaceous. The ophiolite and underlying thrust sheets of distal to proximal oceanic sediments were emplaced a minimum of 250 km SW onto the continental margin. Subduction of Triassic-Jurassic oceanic basalts to c. 10 kbar (c. 39 km depth) led to the accretion of amphibolite-facies rocks to the base of the ophiolite. Thrusting propagated towards the continental margin and ended with subduction of the thinned continental crust to C. 20 kbar (c. 78 km depth), choking the subduction zone. Buoyancy forces caused the rapid exhumation of eclogites, blueschists and carpholite-grade HP rocks along the NE margin of the continental plate. During the later phase of foreland-propagating thin-skinned thrusting in the SW, NE-facing backfolding and backthrusting occurred in the hinterland, with the final exhumation of the HP rocks. Model B follows recent suggestions that a nascent SW-dipping subduction zone, dipping beneath the continental margin, existed between 130 and 95 Ma, prior to formation and emplacement of the ophiolite. A major NE-facing fold-nappe structure in the pre-Permian basement rocks of Saih Hatat is interpreted as reflecting subduction beneath the margin. Two high-pressure metamorphic events have been suggested, the first predating ophiolite emplacement, the second caused by ophiolite loading. This model is untenable, being based on a misinterpretation of the NE-facing structures in northern Saih Hatat, and on some dubious older 40Ar/39Ar cooling ages from the eclogite-facies rocks of As Sifah. We conclude that all structures in northern Oman and all the reliable geochronology point to a single emplacement-obduction event lasting from Cenomanian-Turonian time (c. 95 Ma) when amphibolites were accreted along the metamorphic sole of the ophiolite, to Campanian time, when the continental margin was subducted to the NE producing blueschists and eclogites, to the final thin-skinned emplacement of all thrust sheets, which ended before the Late Maastrichtian, at c. 68 Ma. © Geological Society of London 2003.